(3HZjI GdWdGHs - (3CHh YHO Gddg eMeO Hf CMeO Hf CHj jMji GdJdeSGfj GdMHGc,J (B867 (3g` s
(3ChdgG (B:s
(3HMeOc Gddge fXei CHJOi eUdjkG Ydi GdQShd GdCMeOi hGQJLi Gf jLPdf KhGHi Ydi fXGe HZjI GdWdGH s
(3BNQgG (B:s
(3hai GdPi PcQJg caGjg hGdMeO ddg HdG fgGjI s
(3CQLhRg ai GdESWQdGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B114s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B2255 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B12 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B169(1)) s
Keywords: (3Gdadcs